The Performance of Supporting Laboratories to the Implementation of the Regulation of Minister of Agriculture No. 88 the Year 2011 through Agricultural Quarantine Agency Class I Semarang - Heru Wahyupraja; Susamto Somowiyarjo; Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2022)
The Indonesian government is obliged to ensure the public health of the people of Indonesia by the supervision of Fresh Food Originated from Plant (Pangan Segar Asal Tumbuhan [PSAT]) arriving from abroad. Therefore, the regulation of Minister of Agriculture Number 88 in 2011 was issued to regulate inspection requirement of PSAT. There are some challenges in the implementation of these regulations until 2015, such as the unavailability of accredited laboratories, the lack of communication between stakeholders, and limited human resource or utensil within testing laboratories. Most of the testing laboratories appointed by the government are not yet accredited. Only 60% are able to perform tests mandated listed in The Regulation of Minister of Agriculture No. 88 the Year 2011. On the other hand, private laboratories accredited by ISO/IEC 17025 showed higher capacity by being able to perform 77.8 to 100% of mandated tests. The implementation challenges were later addressed by the revision of the regulation and release of issue Regulation 04/2015 in ref. The Regulation of Minister of Agriculture 13/2016. These regulations acknowledge Food Safety System of the state of origin or their administration of the Testing Laboratory Registration. In other words, they put forward the implementation of supervision in the country of origin reducing Indonesia’s reliability on providing high level of testing laboratories itself. The implementation of The Regulation of Minister of Agriculture 04/2015 in ref. the Regulation of  Minister of Agriculture 13/2016 expected Quarantine Measures on the importation of PSAT to be more effective and efficient. Therefore, impact of the implementation of this new regulation would shorten delay periods for cargo containers in ports (dwelling time), reduce handling cost of containers, minimize laboratory testing fees, and reduce risk of rejection of imported products because of incompliance.